Perbedaan Kadar 25(OH)D Serum, Asupan Vitamin D, Magnesium dan Zink pada Status Gizi Obesitas dan Normal: Differences in Serum 25(OH)D Levels, Intake of Vitamin D, Magnesium, and Zinc in Obese and Normal Nutritional Status - Risanti, Suci Padma; Desmawati, Desmawati; Karmia, Hudila Rifa (Universitas Airlangga, 2024)
Background: Vitamin D deficiency affects about 50% of people worldwide and 95% of Indonesian women of childbearing age. Micronutrient intake can impact serum 25(OH)D levels. Obesity is linked to serum 25(OH)D levels and micronutrients like zinc, magnesium, and vitamin D consumption. Objectives: This study aims to determine the differences in serum levels of 25(OH)D, vitamin D, magnesium, and zinc intakes in obese and normal students at the Faculty of Medicine, Andalas University, Padang. Methods: This research was observational with a comparative case-control design at the Faculty of Medicine and Biomedical Laboratory, Andalas University, from November 2021 to July 2022. Systematic random sampling was used to select the sample, obtaining 64 female students with obesity and normal nutritional status. Data were collected by blood sampling and questionnaires. Bivariate analysis used an independent t-test. Results: The results showed the mean serum levels of 25(OH)D, vitamin D, magnesium, and zinc intakes in the obese group were 10.98 ± 2,12 ng/mL; 5.07 ± 1,47 mcg; 166.04 ± 65.27 mcg and 6.88 ± 2.73 mcg, while the mean in the standard group were 13.94 ± 4.57 ng/mL; 5.92 ± 1.77 mcg; 205.88 ± 92.84 mcg; and 7.62 ± 2.67 mcg. The mean serum levels were 25(OH)D, vitamin D, magnesium, and zinc intakes were lower in the obese group (p-value = 0.001; 0.040; 0.044; 0.280). Conclusions: There are significant differences in serum levels of 25(OH)D, vitamin D, and magnesium in female students with obese and normal nutritional status. There is no significant difference in zinc intake in female students with obese and normal nutritional status.